Identifikasi Faktor-Faktor Iklim Keselamatan Kerja terhadap Kinerja Keselamatan Kerja pada Proyek Konstruksi Di Provinsi Jambi - Darul Kutni; Nasfryzal Carlo; Wayudi P Utama (Jurnal Talenta Sipil, 2023)
Even though the construction sector provides business opportunities for workers, this sector also contributes 30% -40% of accidents and fatalities. For this reason, it is necessary to identify the factors of the work safety climate and their influence on work safety performance. This study aims to identify and measure the work safety factors and safety performance and which dominantly improves safety performance. The third aim to evaluate the relationship model between work safety climate and work safety performance. This research adopts 45 safety climate variables Zahoor, 2017 and uses 275 construction workers in Jambi Province. The data collection techniques with primary (informants) and secondary data (K3 documents and literature studies) utilize observation, direct interviews, and questionnaires. The results study found that the first three factors form the work safety factor (FIK1, FIK 2, FIK3). For  named FIK1 to become Management Commitment and OSH resources, Procedures and Awareness of FIK2, FIK3 is named Perception of Accidents. In the second stage, the research found only factor 3 or IK3, namely the Perception of Accidents that affected safety performance. In the third stage, the study found that the safety performance measurement model only had the third factor, namely the Perception of Accidents, which could be used in a structural equation model that affected safety performance. Hopefully that understanding and knowing the observed variables from CI can help the project management team design the right strategy to create a safe project environment.